Adjunctive therapeutic effects of micronutrient supplementation in inflammatory bowel disease - Wu, Yanrui; Liu, Chuan; Dong, Weiguo (Frontiers in Immunology, 2023)
Growing evidence suggests that micronutrient status may have some impact on the course of inflammatory bowel disease (IBD). However, micronutrient deficiencies are easily overlooked during the treatment of IBD patients. There have been many studies on micronutrient supplementation, in which several clinical trials have been conducted targeting vitamin D and iron, but the current research is still preliminary for other vitamins and minerals. This review provides an overview of the adjunctive therapeutic effects of micronutrient supplementation in IBD, to summarize the available evidence, draw the attention of clinicians to micronutrient monitoring and supplementation in patients with IBD, and also provide some perspectives for future research directions.